Return to Work Program for a Chef with Pemphigus Vulgaris : a Case Report - Soemarko, Dewi; Indri, Olieve (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Background: Pemphigus vulgaris is an autoimmune, intraepithelial, blistering disease, affecting the skin and mucosae, is defined by IgG antibody deposits in the keratinocyte membranes of the epidermis, leading to acantholysis with consequent generation of blisters. This disease has recurrence characteristics triggering by various risk factors such as medications, physical agents, infectious agents, hormones, and stress. The aim of this case report is to manage a return to work program for pemphigus vulgaris patient with numerous, widespread, blisters especially on both hands.Case presentation: Fourty-three years old woman presents with a painful and itchy blisters appeared in the palms, feet and body surfaces which are widely spreading throughout this week. The patient reported that the lesions first appeared as an ulcer in the upper lip, followed by cutaneus involvement. On physical examination, vital signs are normal and nutritional status is overweight. Dermatology status found numerous, widespread, tense or flaccide blisters, erosions and pruritic erythema on chest, back, abdomen, both arms and both palms accompanied by black crust with a soliter erosions on the upper lip. She was diagnosed with Pemphigus Vulgaris since 10 December 2020 and was controlled very well since February 2021, when suddenly new blisters started to appear on May 2022.She has got a medical and occupational management for her disease, which let her recovered and ready to go back to work again. Conclusion: Pemphigus Vulgaris could affect patient’s work life. Multiple hazard in the work place also can affect the nature of the disease. Occupational management is important to help patients return to their former work, and to prevent reccurence. As a return to work program, the author recommended several changes in the workplace to reduce the triggering factor, promote self care, did an education, and showed the way to work with a good ergonomic style. Work related stress which act as an exogenous factor triggering Pemphigus Vulgaris need to be controlled. With appropriate medications and interventions to control her occupational risk and exposure, patients can return to work with some modifications.